Changes in management of owned cats in the countryside – A comparison of results from surveys undertaken in the same rural area of Denmark in 1998 and 2022 - Peter Sandøe; Ulrike Gade; Marianne Lund Ujvári; Bryndis Wöhler; Thomas Bøker Lund; Henrik Meilby; Clare Palmer; Søren Saxmose Nielsen (PLoS ONE, 2025)
This study investigates changes in the management of owned domestic cats (Felis catus) in a rural area of Denmark, at two points in time separated by 24 years. Households in a 47 km2 area, and on 23 farms near this area, were presented with the same questionnaire in 1998 and in 2022. Additional data about the number of cats earmarked/microchipped and registered in 1998 were provided by two cat registers. The study population was compared to other rural areas in Denmark using data collected in 2021 from a nationwide probability survey of cat owners. The study area was found to represent rural areas in Denmark well. From 1998 to 2022, our study found a slight drop in the total number of owned cats. There was a major shift away from cats living on farms; this was true both of full-scale farms (that is, farms from which the farmer makes a living) where the number of cats decreased by two-thirds between 1998 and 2022 compared to 1998; and on hobby farms, where the number halved over the period. However, the number of cats living in residential homes nearly doubled, and, correspondingly, there was also a significant increase in the proportion of cats with indoor access. Cat owners have increasingly adopted measures to manage their cats, including much higher proportions of cats being spayed and castrated (there was an increase from 61% to 98% among male cats with indoor access and from 13% to 70% among male cats without indoor access). There was, also, a major increase in cats that have been earmarked/microchipped and registered, rising from 8% to 64%. This change in owner behaviour has led to many fewer unwanted kittens being born and subsequently killed. The findings therefore provide evidence of changing rural human-cat relationships, with rural cat owners increasingly managing their cats in the same way as urban cat owners. Our findings also help to explain recent evidence that the number of unowned cats in Denmark is much lower than previously assumed.